Digital Art on the Internet: the limits of the Brazilian Legal System and the Global Contemporary Thinking - Villefort, Wisrah (Brazilian Journal of Operations & Production Management, 2018)
This study aims at reaching the emerging global thinking around the relations of access to digital artistic content available on the internet. Through the appointments of the intersection between the knowledges of the law, anthropology, philosophy, physics and art - organized in a multidisciplinary way - the present scientific narrative is build. Initially, a brief history of the idea of constructing copyright in the global context is presented. Subsequently, the digital object is analyzed as material to produce art in the contemporary context. Then, the post-internet cultural phenomenon is observed, so that the current Brazilian Copyright Law System can be inquired due its limits and openings. Finally, the ’Creative Commons’ is presented analytically in the face of current demands in the follow of the contemporary understanding around copyright.